A degenerative process underlying hierarchic transitions in evolution. (December 2022) - Deacon, Terrence W.
Abstract: This paper describes an evolutionary process likely involved in hierarchic transitions in biological evolution at many levels, from genetics to social organization. It is related to the evolutionary process described as contingent neutral evolution (CNE). It involves a sequence of stages initiated by the spontaneous appearance of functional redundancy. This redundancy can be the result of gene duplication, symbiosis, cell-cell interactions, environmental supports, etc. The availability of redundant sources of biological functionality relaxes purifying selection and allows degenerative changes to accumulate in one or more of the duplicates, potentially degrading or otherwise fractionating its function. This degeneration will be effectively neutral so long as another maintains functional integrity. Sexual recombination can potentially sample different combinations of these sub functional alternatives, with the result that favorable synergistic interactions between independently degenerate duplicates will have a non-negligible probability of being uncovered. The expression of such a synergistic combinatorial effect will result in the irreversible degradation of any remaining autonomous functionality, thereby initiating selection to prevent breakup of co-dependency. This becomes relevant to the evolution of hierarchic transitions when two or more organisms reciprocally duplicate functions that each other requires. If the resulting relaxation of selection reliably persists for an extended evolutionary period it will tend to produce complementary degenerative effects in each organism, leading to their irreversible codependency and purifying selection to avoid loss of integrity of their higher order functional unity. This provides a partial inversion of Darwinian logic that explains how the potential costs of the loss of organism autonomy can be mitigated, enabling the incremental transition to a synergistic higher order unit of evolution.